On the state of involvement of Kazakhstani workers in the management of the organization - Ahmetzhan, L.Z. (Bulletin of the Karaganda University “Law Series”, 2021)
The article provides an assessment of the legal support of involvement of Kazakhstani workers in the management of an organization. The relevance of study lies in the need to increase the level of legal protection of the rights and interests of workers. The assessment is based on the results of questionnaires, analytical studies and the existing database. The institution of employee involvement in the management of an organization is also known under the term “industrial democracy”. A plenty of studies by foreign authors are devoted to the issues of legal support, the results of the practical implementation of forms of management by employees. This is due to the normative and legal consolidation of elements of industrial democracy in a number of documents of the International Labour Organization. The studies, to a greater extent, have been devoted to the impact of the development of elements of industrial democracy in organizations on the indicators of their stability, development, productivity, competitiveness, etc. The results of these studies are to highlight the positive impact of the practice of employee participation in the management of an organization on various spheres of financial and economic activity. At the same time, similar studies have not been conducted on the Kazakhstani business community, which has its own distinctive features of functioning and development. Consequently, this article is devoted to filling this gap. Based on the results of the study conclusions and proposals were formulated, recommendations were given for enhancing the development of the practice of employee participation in the management of the organization as one of the most effective methods of protecting the rights of employees, as well as increasing the sustainability and development rates of the socio-economic indicators of the organization.